Urgensi Prinsip Kepatutan dan Keadilan (Redelijkheid en Billijkheid) Dalam Pembuatan Perjanjian Pendahuluan - Ragil Kusnaning Rini (Notaire, 2021)
The principle of reasonableness and fairness (redelijkheid en billijkheid) is a pair of principles that are closely related and constitute an interpretation of the principle of good faith. So that the terms used in NBW are no longer good faith, but rather reasonableness and fairness. In the Netherlands, this principle is mandatory not only at the time of contract execution, but also at the pre-contract stage, giving rise to pre-contractual liability. Whereas to judge whether or not a preliminary agreement is binding, what must be observed first is the substance and not just based on the title. The importance of applying the principles of reasonableness and fairness in the preliminary agreement is to realize contractual justice and provide protection for weak parties when the expectations of the promises offered cannot be fulfilled. In essence, the principle of reasonableness and fairness requires proportionality among the parties. A preliminary agreement if the clauses are made without paying attention to the principles of reasonableness and fairness will have the potential to cause disputes. Furthermore, the party who feels aggrieved can file a lawsuit on the basis of an unlawful act and demand compensation for the costs that have been incurred.Keywords: Preliminary Agreements; Good Faith; Redelijkheid en Billijkheid.Prinsip kepatutan dan keadilan (redelijkheid en billijkheid) merupakan sepasang prinsip yang saling terkait erat dan merupakan penafsiran dari makna prinsip itikad baik. Sehingga istilah yang digunakan pada NBW tidak lagi itikad baik (good faith), melainkan kepatutan dan keadilan (reasonableness and fairness). Di Belanda, prinsip ini tidak hanya diwajibkan pada saat pelaksanaan kontrak saja, namun juga pada tahapan pra kontrak sehingga menimbulkan adanya pra-contractual liability. Bahwa untuk menilai mengikat atau tidaknya suatu perjanjian pendahuluan, maka yang harus dicermati terlebih dahulu adalah substansinya dan bukan hanya didasarkan pada judulnya saja. Pentingnya penerapan prinsip kepatutan dan keadilan dalam perjanjian pendahuluan adalah untuk mewujudkan keadilan berkontrak dan memberikan perlindungan terhadap pihak yang lemah manakala harapan dari janji-janji yang ditawarkan tidak dapat terpenuhi. Pada hakikatnya prinsip kepatutan dan keadilan menghendaki adanya proporsionalitas diantara para pihak. Suatu perjanjian pendahuluan jika klausul-klausulnya dibuat tanpa memperhatikan prinsip kepatutan dan keadilan akan berpotensi menimbulkan perselisihan. Selanjutnya terhadap pihak yang merasa dirugikan dapat mengajukan gugatan atas dasar perbuatan melanggar hukum dan menuntut ganti kerugian atas biaya-biaya yang telah dikeluarkannya.Kata Kunci: Perjanjian Pendahuluan; Itikad Baik; Redelijkheid en Billijkheid.